2015
DOI: 10.1002/jor.22949
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic analysis of knee synovial fluid as a potential diagnostic approach for osteoarthritis

Abstract: Osteoarthritis (OA) is a leading cause of chronic joint pain in the older human population. Diagnosis of OA at an earlier stage may enable the development of new treatments to one day effectively modify the progression and prognosis of the disease. In this work, we explore whether an integrated metabolomics approach could be utilized for the diagnosis of OA. Synovial fluid (SF) samples were collected from symptomatic chronic knee OA patients and normal human cadaveric knee joints. The samples were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 38 publications
1
87
0
Order By: Relevance
“…All prior metabolomic studies in humans have been cross-sectional in nature comparing individuals with or without OA using either urine 18, 40 , serum 19 , synovial fluid 41 or plasma 20 . An NMR-based urine metabolomics study that used samples from the Johnston County Osteoarthritis project found differences in participants with radiographic hip or knee OA from controls and noted a correlation of a metabolite profile with radiographic OA severity 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All prior metabolomic studies in humans have been cross-sectional in nature comparing individuals with or without OA using either urine 18, 40 , serum 19 , synovial fluid 41 or plasma 20 . An NMR-based urine metabolomics study that used samples from the Johnston County Osteoarthritis project found differences in participants with radiographic hip or knee OA from controls and noted a correlation of a metabolite profile with radiographic OA severity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Adams et al 43 analyzed conditioned media from cultures of synovial explants obtained from early and end-stage OA joints and noted differences in metabolites associated with collagen degradation, amino acid and branched-chain amino acid catabolism, energy metabolism and lipid and carbohydrate metabolism. Metabolic profiling using synovial fluid collected from 55 knee OA patients and 13 cadaveric controls, revealed 11 metabolites that separated the two groups 41 . None of the 11 metabolites identified in synovial fluid matched those found in the urine samples from our progression study or those found in plasma samples from a cross-sectional study of knee OA 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In a large variety of ethnic groups, the study found that the levels of hyaluronic acid were significantly higher in males than that of females [24]. Another study, which included 291 white patients with OA of the knee, it was found a significant increase in blood COMP levels in patients with K-L and consistent with the patient's score [18]. In 324 postmenopausal women, the study showed that the level of II CTX in different parts of OA was different, which suggested that OA can be identified in different parts of the patient [25].…”
Section: Study On the Clinical Value Of Mirna98b As A Potential Biomamentioning
confidence: 87%
“…Because there is a lack of specificity and sensitivity of the biological markers of osteoarthritis [18], therefore, this study explores the possibility of miRNA98b as a biomarker for early diagnosis and prognosis of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have utilized urine 39,40 , serum 41,46 , synovial fluid 38,4245 or media from the culture of synovial explants 47 to compare between groups and have led to the identification of a number of metabolites that may prove valuable as biomarkers for OA. These metabolites include dimethyl sulfone 46 , glutamine 47 , tryptophan 41 and carnitine 42 .…”
Section: Introductionmentioning
confidence: 99%